A NEW APPROACH TO THE ISSUE OF WOMEN IN THE SOCIAL STRATIFICATION OF SOCIETY (1900-1930 s) - Ismoilova Nigorakhon Usmonjanovna (Modern American Journals, 2025)
This study examines the role of women in the social stratification of Turkestan (present-day Uzbekistan) during the early 20th century (1900–1930s), focusing on the impact of Russian imperial and early Soviet policies on women’s social, educational, and cultural positions. The research analyzes how women’s participation in education, literacy programs, and socio-political activities was shaped by colonial and Soviet administrative-command systems, ideological goals, and modernization efforts. The study highlights both the quantitative achievements-such as increased literacy and the emergence of the first generations of female teachers and intellectuals-and the qualitative challenges, including cultural disruption, politicization, and repression of traditional female roles. This work adopts a new methodological approach to assess women’s historical position, using archival sources, scientific literature, and periodicals from the Russian Empire and early Soviet Turkestan.
Keywords: Women’s emancipation; social stratification; Soviet Uzbekistan; Turkestan; education; modernization; cultural transformation; gender roles; 1900–1930s; colonial policy.